Analysis of the Clinical Outcome of Microlumbar Decompression in Degenerative Grade-1 Spondylolisthesis versus Stable Lumbar Canal Stenosis - Singh, Ajaybir (Revista Brasileira de Ortopedia, 2025)
To assess the clinical outcomes of a non-fusion decompression procedure in degenerative low-grade spondylolisthesis versus stable lumbar canal stenosis.The study analyzed 50 cases of lumbar degenerative pathology that underwent decompression involving a single level. Dynamic X-ray assessment was employed to evaluate instability. Group 1 included stable lumbar stenosis, while group 2 included Meyerding grade-1 degenerative spondylolisthesis. Two years postmicrolumbar decompression, the final functional outcomes were assessed using the Oswestry Disability Index (ODI) and the Visual Analog Scale (VAS) for backache and leg pain.Group 1 included 25 cases with a mean ODI of 75.36 ± 13.59, mean VAS for backache of 5.92 ± 3.45, and mean VAS for leg pain of 8.92 ± 1.81. Group 2 included 25 cases with a mean ODI of 68.75 ± 11.81, mean VAS backache of 8 ± 1.22, and mean VAS leg pain of 7.87 ± 1.57. At 2 years, group 1's mean ODI improved to 22.64 ± 17.2 (p < 0.0001), mean VAS backache reduced to 2.04 ± 1.86 (p = 0.0002), and VAS leg pain reduced to 1.56 ± 1.97 (p < 0.0001). Group 2 showed a mean ODI of 24 ± 10.6 (p < 0.0001), backache mean VAS of 2.12 ± 1.43 (p = 0.0009), and mean VAS leg pain of 2.56 ± 1.35 (p = 0.0008). Both groups showed statistically comparable functional improvement.Microlumbar decompression yielded comparable functional outcomes in both groups. This procedure presents a viable option for preserving the integrity of lumbar motion segment in degenerative low grade (Meyerding grade 1) spondylolisthesis.
Keywords: intervertebral disc degeneration; low back pain; sciatica; spinal diseases; spondylolisthesis